TINJAUAN HUKUM ATAS KEWENANGAN KREDITOR MENGAJUKAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG BERDASARKAN UNDANG-UNDANG NOMOR 37 TAHUN 2004 - Jimmy Simanjuntak (Fakultas Hukum Universitas Kristen Indonesia, 2023)
: In essence, petition of suspension of debt payment under Indonesian Law (“PKPU) was designed for the achievement of peace between debtor and creditors through homologation. As regulated on Article 222 (3) Indonesian Law Number 37 Year 2004 concerning Bankruptcy and Suspension of Debt Payment (“UU KPKPU”), competency to submit petition of suspension of debt payment was given not only to debtor but also given to creditors. This provision, however, has loopholes that might be misapplied by creditors who did not seek for peace but merely want to collect the debt, which did not aligned with the main purpose of PKPU. This research aims to provide an in-depth analysis concerning the conformity between creditor’s right to submit petition of PKPU under Article 222 (3) UU KPKPU and peace concept of PKPU.